2018
DOI: 10.1155/2018/4138560
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Endogenous Kallistatin in Vascular Injury and Senescence by Inhibiting Oxidative Stress and Inflammation

Abstract: Kallistatin was identified in human plasma as a tissue kallikrein-binding protein and a serine proteinase inhibitor. Kallistatin exerts pleiotropic effects on angiogenesis, oxidative stress, inflammation, apoptosis, fibrosis, and tumor growth. Kallistatin levels are markedly reduced in patients with coronary artery disease, sepsis, diabetic retinopathy, inflammatory bowel disease, pneumonia, and cancer. Moreover, plasma kallistatin levels are positively associated with leukocyte telomere length in young Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 63 publications
1
33
0
2
Order By: Relevance
“…One of them is that the number of EPCs has decreased signi cantly when long-term exposure to the condition of hyperlipidemia and hyperglycemia [21]. The other is that EPCs therapy is compromised by the CD34-positive cells differentiation into smooth muscle progenitor cells (SMPC) and decreased function of EPCs mainly due to in ammatory cascade in the harsh environment, which in turn inhibits vascular repair and reendothelialization [22][23][24][25]. Thus, to circumvent these problems, many approaches have been attempted to enhance EPCs functions.…”
Section: Discussionmentioning
confidence: 99%
“…One of them is that the number of EPCs has decreased signi cantly when long-term exposure to the condition of hyperlipidemia and hyperglycemia [21]. The other is that EPCs therapy is compromised by the CD34-positive cells differentiation into smooth muscle progenitor cells (SMPC) and decreased function of EPCs mainly due to in ammatory cascade in the harsh environment, which in turn inhibits vascular repair and reendothelialization [22][23][24][25]. Thus, to circumvent these problems, many approaches have been attempted to enhance EPCs functions.…”
Section: Discussionmentioning
confidence: 99%
“…Kallistatin is a unique serine protease inhibitor (serpin family A member 4) and was one of several serpins elevated during the Antarctica trek and five weeks of recovery. Kallistatin has many roles including suppression of cytokine signaling expression in macrophages [37,38]. Kallistatin antagonizes tumor necrosis factor (TNF)-α induced inflammation, oxidative stress, and apoptosis while enhancing bacterial clearance and exerting anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Kallistatin antagonizes tumor necrosis factor (TNF)-α induced inflammation, oxidative stress, and apoptosis while enhancing bacterial clearance and exerting anti-inflammatory effects. The elevation of kallistatin during the Antarctica trek and recovery appears to represent one attempt by the immune system to restore homeostasis [38].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that angiogenesis is associated with various biological processes and pathways in DR, such as the mitogen-activated protein kinase signaling pathway [ 8 ] and the tumour necrosis factor signaling pathway [ 9 ]. Animal experiments indicated that anti-angiogenic therapy in early DR may have a positive effect on the prognosis [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%